Determinant of Employee Engagement and Its Implications on Employee Performance - Meswantri, Meswantri; Ilyas, Awaludin (International Review of Management and Marketing, 2018)
This study aims to analyze and prove partially or simultaneously the influence of transformational leadership, employee placement, competence and employee engagement on employee performance in construction and building companies in DKI Jakarta. The research method used in this research is descriptive quantitative method of causal approach from sample size of 237 respondents; data analysis method used is SEM (Structural Equation Modeling) through Lisrel Program. Based on the results of the research, found that transformational leadership, employee placement and competence either partially or simultaneously have positive and significant effect on employee engagement with coefficient of determination (R2) of 51%. Similarly, transformational leadership, employee placement, competence and employee engagement either partially or simultaneously have a positive and significant effect on employee performance with the value of determination coefficient (R2) of 85%. To improve the performance of employees required the implementation of good transformational leadership, employee placement tailored to the potential and talents for employees, the competencies need to be improved and employee engagement should be improved. Keywords: Transformational Leadership, Employee Placement, Competency, Employee Engagement, Employee Performance JEL Classiofications: M12, M21, M52